Autonomy in Language Learning and Teaching New Research Agendas (Palgrave Macmillan UK, 2018)
This book seeks to expand the research agendas on autonomy in language learning and teaching in diverse contexts, by examining the present landscape of established studies, identifying research gaps and providing practical future research directions. Based on empirical studies, it explores research agendas in five emerging domains: language learning and teaching in developing countries; social censure and teacher autonomy; learner autonomy and groups; learner autonomy and digital practice; and finally, learner autonomy and space. In doing so, it sheds new light on the impact of digital media, group dynamics and the application of ecological perspectives on learner autonomy. The contributors present a novel reconsideration of new learning affordances, and their discussion of spatial dimensions provides much needed expansion in the field. This book will have international appeal and provide an invaluable resource for students and scholars of second language learning and higher education, as well as teacher educators. Alice Chik is Senior Lecturer in Educational Studies at Macquarie University, Australia. Naoko Aoki is Professor of the Graduate School of Letters, Osaka University, Japan, where she teaches Japanese as a second language pedagogy. Richard Smith is a Reader and Associate Professor at the University of Warwick, UK. Chapter 2 of this book is open access under a CC BY 4.0 license via link.springer.com. .